The Influence of web quality and sales promotion toward impulse buying behavior with openness personality as moderating variable - Fatiha Rahmalita Fitri (Jurnal Akuntansi, Manajemen dan Ekonomi, 2018)
To meet daily wants and needs, consumer conducted shopping. The development and innovation of technology in this era resulted shopping no longer only done in supermarket, shopping centre, etc. Nowadays, shopping also can be done by online via internet. There are so many online shopping website in Indonesia, one of them is Shopee. Shopee entered market in Indonesia on May 2015 and started operated on June 2015. The purpose of this research to analysis the component of web quality and sales promotion influenced impulse buying behaviour with openness personality as moderating variable. Research methodology used for this research is a case study with survey research method. Convenience sampling techniques that come from non probability sampling techniques are used for the selection of sample. The research sample is 130, comes from consumers of Shopee around Indonesia. Method of processing data using SEM with AMOS used to analysis the data. This research implicated for start-up company based in online; Because the company could be develop, improved the quality, and create new innovation related to the result of research. The limitation of this research is the result of goodness index of fit in all variables are still in the marginal category.